Linking clinician interaction and coordination to clinical performance in Patient-Aligned Care Teams. (December 2015) - Hysong, Sylvia; Thomas, Candice; Spitzmüller, Christiane; Amspoker, Amber; Woodard, LeChauncy; Modi, Varsha; Naik, Aanand
Abstract Background Team coordination within clinical care settings is a critical component of effective patient care. Less is known about the extent, effectiveness, and impact of coordination activities among professionals within VA Patient-Aligned Care Teams (PACTs). This study will address these gaps by describing the specific, fundamental tasks and practices involved in PACT coordination, their impact on performance measures, and the role of coordination task complexity. Methods/design First, we will use a web-based survey of coordination practices among 1600 PACTs in the national VHA. Survey findings will characterize PACT coordination practices and assess their association with clinical performance measures. Functional job analysis, using 6–8 subject matter experts who are 3rd and 4th year residents in VA Primary Care rotations, will be utilized to identify the tasks involved in completing clinical performance measures to standard. From this, expert ratings of coordination complexity will be used to determine the level of coordinative complexity required for each of the clinical performance measures drawn from the VA External Peer Review Program (EPRP). For objective 3, data collected from the first two methods will evaluate the effect of clinical complexity on the relationships between measures of PACT coordination and their ratings on the clinical performance measures. Discussion Results from this study will support successful implementation of coordinated team-based work in clinical settings by providing knowledge regarding which aspects of care require the most complex levels of coordination and how specific coordination practices impact clinical performance.